1967
DOI: 10.1111/j.1365-2621.1967.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Stability of Nitric Oxide Myoglobin I. Studies with Model Systems

Abstract: SUMMARY— The rate and extent of the formation of nitric oxide myoglobin (NOMb) were studied in aqueous model solutions containing 1–1.5 mg Mb per ml, to which various substances were added to study their effect. Conversion of Mb to NOMb was optimum when 1 mol sodium nitrite per mol Mb was present, provided that the solution contained optimum sodium ascorbate (200 mob). Results were the same with sodium erythorbate, ascorbic acid, and erythorbic acid. Cysteine also furthers the formation of NOMb; its optimum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1970
1970
1994
1994

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…If the nitrite depletion due to the addition of metal ions is a reductive process, it would seem logical that more nitric oxide would be produced leading to increased amounts of nitrosylhemochrome. It is well known that ferrous, ferric, cupric and zinc ions enhance the formation of cured color in model systems (Weiss et al 1953;Siedler and Schweigert 1959;Reith and Szakaly 1967). However, results in Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…If the nitrite depletion due to the addition of metal ions is a reductive process, it would seem logical that more nitric oxide would be produced leading to increased amounts of nitrosylhemochrome. It is well known that ferrous, ferric, cupric and zinc ions enhance the formation of cured color in model systems (Weiss et al 1953;Siedler and Schweigert 1959;Reith and Szakaly 1967). However, results in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Gibson (1943) showed that metal ions (CU++ and Fe"+) exerted a catalytic effect on the rate of reduction of methemoglobin in the presence of ascorbic acid. Since then, several studies have revealed the enhancing effect of metal ions such as Fe++, Fe"' , Cu++ and Zn"in the presence of ascorbic acid (Weiss et al 1953), and Fe++ in the presence of cysteine or ascorbic acid (Sielder and Schweigert 1959;Reith and Szakaly 1967) pigment. Seman et al (1980) showed that partial replacement of NaCl by MgC12 or KCl in bologna preparation was possible without impairing the functionality of NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to measurable nitrite, another indication of formation of NOCl and increased nitrosating ability would be enhanced production of nitrosyl heme pigments due to increased production of the nitrosoreductant intermediates. If significant NOCl is formed, increased nitrosating activity should result in increased nitric oxide and subsequent nitrosyl heme formation Reith and Szakaly (1967a). reported that salt had an adverse effect on the color intensity and formation of nitrosylmyoglobin in model systems consisting of myoglobin, nitrite, ascorbate, and sodium chloride, whereasFujimaki et al (1975) showed that sodium chloride increased residual nitrite, enhanced development of color, and decreased the level of nitrate in model systems with the same components as mentioned previously but at different molar ratios.…”
mentioning
confidence: 87%